Vesicoureteric reflux: Evaluation by bladder volume graded direct radionuclide cystogram - Agrawal Vikesh; Rangarajan Venkatesh; Kamath Tejaswini; Borwankar S (Wolters Kluwer Medknow Publications, 2009)
Aim : Evaluation of vesicoureteric reflux (VUR) in children by bladder volume graded direct radionuclide cystogram (BVG DRC). This technique allows detection of VUR at different bladder volume grades. Materials and Methods : In this prospective study, 33 patients (66 renal units) with suspected vesicoureteric reflux were subjected to a voiding cystourethrogram (VCUG) and BVG DRC. The patients were assessed further with radioisotope renal scans for renal cortical scars. Results : Twenty-two patients and 36 renal units were found to have VUR in either of the reflux studies. A VCUG was able to detect 20 units (55.50%) and a BVG DRC was able to detect 35 units (97.2%). A VCUG had a test accuracy of 77.8% and a BVG DRC had a test accuracy of 98.6%. There was a positive correlation between bladder volume grades and scarring on a DMSA scan. Conclusions : Like a conventional DRC, BVG DRC is a sensitive and an accurate test. It gives additional information on the reflux phenomenon with respect to bladder filling. The bladder volume graded technique is better than conventional DRC for grading of VUR.